Химическая технология. В 2 ч. Ч. 2. Важнейшие химические производства: пер. с рус.; [учебное пособие] - Мухленов И. П. Иван Петрович; Авербух А. Я. Анатолий Яковлевич; Кузнецов Д. А. Дмитрий Афанасьевич; Амелин А. Г. Анатолий Гаврилович; Тумаркина Е. С. Евгения Семеновна; Фурмер И. Э. Изабелла Эмануиловна (Москва, Мир, 1979)
На английском языке